Cognitive Vulnerability in Aging May Be Modulated by Education and Reserve in Healthy People - Roldán-Tapia, María D.; Cánovas, Rosa; León, Irene; García-Garcia, Juan (Frontiers in Aging Neuroscience, 2017)
Aging is related to a deterioration of cognitive performance and to multiple alterations in the brain. Even before the beginning of a noticeable cognitive decline, the framework which holds cognitive function experiences these alterations. From a system-vulnerability point of view of cognition, the deterioration associated with age would be the collection of repercussions during a life. Brain function and structure are modified in a multidimensional way, which could concern different aspects like structural integrity, functional activity, connectivity or glucose metabolism. From this point of view, the effects of aging could affect the most brain systems and their functional activity. In this study, we analyse the functional development of three cognitive domains in relation to aging, educational level and cognitive reserve. A total of 172 healthy subjects were divided into two age groups (young and old), and completed a battery of classic neuropsychological tests. The tests were organized and analysed according to three cognitive domains: working memory and flexibility, visuo-constructive functions and declarative memory. Subjects also completed a questionnaire on cognitive reserve. Results showed that the performance in all cognitive domains decreased with age. In particular, tests related to working memory, flexibility and visuo-constructive abilities were influenced by age. Nevertheless, this effect was attenuated by effects of education, mainly in visuo-constructive domain. Surprisingly, visual as well as verbal memory tests were not affected either by aging, education or cognitive reserve. Brain plasticity plays a prominent role in the aging process, but, as other studies have shown, the plasticity mechanism is quite different in healthy vs. pathological brains. Moreover, this plasticity brain mechanism could be modulated by education and cognitive reserve. Specially, cognitive domains as working memory, some executive functions and the visuo-constructive abilities seem to be modulated by education. Therefore, it seems to be crucial, to propose mechanisms of maintenance of a healthy and enriched brain, since it promotes auto regulatory mechanisms of well-aging.